Plasma concentrations of heroin and morphine-related metabolites after intranasal and intramuscular administration - Skopp, Gisela; Ganßmann, Beate; Cone, Edward J.; Aderjan, Rolf (Journal of analytical toxicology, 1997)
The disposition of heroin and its metabolites was investigated in four healthy male volunteers following intranasal administration of 6 and 12 mg heroin hydrochloride. In addition, two doses of 6 mg heroin hydrochloride were injected intramuscularly for comparison of pharmacokinetic parameters. Serum samples were analyzed for heroin, 6-acetylmorphine, and morphine by solid-phase extraction-gas chromatography-mass spectrometry. The concentration of morphine glucuronides was determined by high-performance liquid chromatography based on the native fluorescence of the conjugates. Major findings were rapidly rising and declining terminal phases for heroin and 6-acetylmorphine and slowly declining phases of morphine and metabolites after both routes of administration. The area under the curve values of morphine-3-glucuronide depended on dose but not on route of administration. The apparent terminal half-lives of morphine-3-glucuronide ranged from 2.2 to 5.2 h for intranasally administered heroin and were 3.0 and 1.7 h for the intramuscularly applied drug. A mean morphine-3-glucuronide-heroin:area-under-curve ratio of 93 for the intranasal route as compared with 38 for the intramuscular route demonstrated that circulating amounts of heroin were about half the size after intranasal administration of the same dose.
Gesehen am 10.08.2023